2020
DOI: 10.17485/ijed/v8.27
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis on the impact of non-performing loans on investment and economic growth and the role of political governance

Abstract: Objective: To empirically analyze the link between nonperforming loans and investments along with the role of political governance. The estimation technique used is the fixed effects model including both the country and timMethods: e fixed effects. The dataset consists a panel of 103 countries with annual data over the period from 2000 to 2017. A unique composite political governance index has been prepared combining the six existing governance indicators via Principal Component Analysis (PCA). Findings: It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
(97 reference statements)
1
0
0
Order By: Relevance
“…SenGupta (2020) did a study using data from a panel of 103 countries with annual data from 2000-2017 and the Fixed Effects model. The study empirically confirmed the theory of the negative impacts of NPLs on the economy [44].…”
Section: -2-empirical Findings On the Impact Of Macroeconomic Determi...supporting
confidence: 75%
“…SenGupta (2020) did a study using data from a panel of 103 countries with annual data from 2000-2017 and the Fixed Effects model. The study empirically confirmed the theory of the negative impacts of NPLs on the economy [44].…”
Section: -2-empirical Findings On the Impact Of Macroeconomic Determi...supporting
confidence: 75%